Incidence of cutaneous graft‐versus‐host disease in a Singapore academic medical centre – A retrospective cohort study. (16th January 2023) - Tan, Wen Hao; Ho, Aloysius; Kadir, Hanis Abdul; Zin, That Khaing; Jordan, Hwang Chung Cheng; Lee, Haur Yueh; Pang, Shiu Ming; Yeo, Yi Wei; Choo, Karen Jui Lin; Oh, Choon Chiat
Abstract: Background: Cutaneous graft‐versus‐host disease (GVHD) is common in allogeneic haematopoietic stem cell transplantation. HLA mismatch is the most significant determinant of GVHD. Our study aimed to compare the incidence of cutaneous GVHD haploidentical (Haplo) and matched donors in an Asian population. Methods: Retrospective cohort study of the 2015–2019 bone marrow transplant registry was conducted in a transplant centre. We compared the incidence of cutaneous GVHD in Haplo with allogeneic matched unrelated donor (MUD) and matched–sibling donor (MSD) transplant recipients. Secondary objectives include acute and chronic GVHD incidence, dermatology referrals, and histological findings. Results: One hundred and seventy‐nine out of 203 cases were reviewed; 17 (9.5%) Haplo, 80 (44.7%) MUDs and 82 (45.8%) MSDs. The median follow‐up for Haplo, MUD and MSD was 15.2, 34.2 and 35.7 months, respectively. Haplo had a higher cumulative incidence of cutaneous GVHD than MUD and MSD ( p = 0.053). Chronic GVHD was only reported in MSD. The most common histology was vacuolar interface changes (13 [44.8%]) with a wide range of onset post‐transplant (19–456 days). Conclusions: Haplo donors may have a higher GVHD incidence than MUD and MSD in our predominantly Asian cohort. This information may be helpful when counselling patients pre‐transplant. Further prospective studies are required.